(untitled) (Papeles, 2021)
In May 2019, the provincial government of Frente Progresista Cívico y Social presented the Plan Abre experience documented in a synthesis book in which it is stated that: The Plan Abre proposes an innovative way to build from the territories, focusing on the needs and rights of the subjects that inhabit each of the neighborhoods (Government of Santa Fe, 2019: 54). Throughout this text (just over 250 pages), reference is made in more than 80 times to the innovation characteristic of the policy. What does it allude to? What dimensions of the Plan can be highlighted from that point of view? What kinds of innovations are bringing into play? What limitations are revealed? From the documentary analysis of the Plan Abre, in the 2014-2019 period, from a synchronic and exploratory perspective, we propose in this article to analyze the characteristics of innovation in design and the implementation of the Plan Abre of the Santa Fe Province as an integral social policy showing why it is a policy of substantial innovation or innovativeness.